Effectiveness of Walking Sport to Sleep Quality of Pregnant Women on The Third Trimester in Silir Village, Wates, Kediri - Anggrawati Wulandari; Erma Retnaningtyas; Erna Kusuma Wardani (Journal for Quality in Women's Health, 2018)
The third trimester pregnant women often get problems such as sleep disorders. This could be due to the increase of anxiety or worry and physical discomfort. One way to overcome is walking. The purpose of this research was to determine the effectiveness of walking sport to sleep quality of pregnant women on the third trimester in Silir village, Wates, Kediri. The research design used was pre-eksperimental with one-group pre-post test design. The total sample of 9 respondents taken by purposive sampling method and using data analysis with Mc Nemar Test. Independent variable that walking and dependent variable that sleep quality of pregnant women on the third trimester. Before walking got 4 respondents (44.4%) have good quality in sleeping and 5 respondents (55.6%) had bad sleep quality. After walking obtained 8 respondents have good quality sleep, but is 1 respondent (11.1%) still have bad sleep quality. The result of the analysis using Mc Nemar Test indicate that obtained p value = 0.025 <ɑ 0.05, so that H0 rejected and H1 accepted which means walking sport effective toward the sleep quality of pregnant women on the third trimester in Silir Village, Wates, Kediri. Doing walking regularly can improve the quality of sleep during pregnancy, because there will be endorphin hormone that make people happy. Walk during the morning before 9 a.m will trigger the serotonin hormone, which makes a more positive mood and how to think more calmly